2019
DOI: 10.3389/fpsyg.2019.02324
|View full text |Cite
|
Sign up to set email alerts
|

Personality in Zoo-Hatched Blanding’s Turtles Affects Behavior and Survival After Reintroduction Into the Wild

Abstract: Reintroduction programs in which captive-bred or reared animals are released into natural habitats are considered a key approach for conservation; however, success rates have generally been low. Accounting for factors that enable individual animals to have a greater chance of survival can not only improve overall conservation outcomes but can also impact the welfare of the individual animals involved. One such factor may be individual personality, and personality research is a growing field. We designed a proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…In this sense, personality has been shown to have an influence on success on breeding in black rhinoceros ( Diceros bicornis; Carlstead et al, 1999), blue tits ( Cyanistes caeruleus ; Mutzel et al, 2013), or giant pandas ( Ailuropoda melanoleuca ; Powell et al, 2008) among others, where in the case of felids, nonbreeder cheetahs were found to score significantly higher on tense-fearful factor than breeder cheetahs (Wielebnowski, 1999). Likewise, it has been found that personality plays a role on successful reintroduction in Blanding’s turtles ( Emydoidea blandingii; Allard et al, 2019), European minks ( Mustela lutreola ; Haage et al, 2017), or wood mouses ( Apodemus sylvaticus; Stratton, 2015), among others. In absence of examples on felids, the swift foxes ( Vulpex velox ) boldness was related with early death after the reintroduction of captive-bred animals (Bremner-Harrison et al, 2004); while with the Tasmanian devils ( Sarcophilus harrissii) boldness was related with higher survival rates (Sinn et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, personality has been shown to have an influence on success on breeding in black rhinoceros ( Diceros bicornis; Carlstead et al, 1999), blue tits ( Cyanistes caeruleus ; Mutzel et al, 2013), or giant pandas ( Ailuropoda melanoleuca ; Powell et al, 2008) among others, where in the case of felids, nonbreeder cheetahs were found to score significantly higher on tense-fearful factor than breeder cheetahs (Wielebnowski, 1999). Likewise, it has been found that personality plays a role on successful reintroduction in Blanding’s turtles ( Emydoidea blandingii; Allard et al, 2019), European minks ( Mustela lutreola ; Haage et al, 2017), or wood mouses ( Apodemus sylvaticus; Stratton, 2015), among others. In absence of examples on felids, the swift foxes ( Vulpex velox ) boldness was related with early death after the reintroduction of captive-bred animals (Bremner-Harrison et al, 2004); while with the Tasmanian devils ( Sarcophilus harrissii) boldness was related with higher survival rates (Sinn et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, why did this happen and is this true for all species? After the publication of this study, there have been calls in the literature to include personality assessment in translocations/animal releases, and boldness, exploration, activity, and sociability became the most studied aspects of personality-conservation dyad [ 41 , 67 , 68 , 69 ].…”
Section: Animal Personality and Animal Releasesmentioning
confidence: 99%
“…Bolder animals are more prone to take risks, because they explore more their environment, get closer to predators, sample more food items, etc. [ 66 , 68 , 70 ]. By doing this, bolder animals may die sooner than shyer animals [ 66 ].…”
Section: Animal Personality and Animal Releasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the lack of success in reproduction can be a sign of the individual not being able to express species-specific behaviour, which can indicate lack of animal welfare (Gusset & Macdonald 2010;Yordy & Mossotti 2016). When looking at personality, there are signs of difference in personality between individuals based on significant difference in behavioural reaction patterns, which can indicate animal welfare (Allard et al 2019).…”
Section: Assessing Welfare Among the Awdsmentioning
confidence: 99%